2009
DOI: 10.1504/ijmc.2009.022440
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effectiveness of text vs. multimedia Location-Based Advertising messaging

Abstract: The emergence of mobile communication and positioning technologies has presented advertisers and marketers with a radically innovative advertising channel: Location-Based Advertising (LBA). Despite the growing attention given to LBA, little is understood about the differential effects of text and multimedia advertising formats on the mobile consumer perceptions and behaviours. This exploratory study empirically examines the effects of multimedia advertisements vis-à-vis text-based advertisements on consumer pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(166 citation statements)
references
References 59 publications
7
146
0
13
Order By: Relevance
“…Comparing MMS with SMS, multimedia appeared to have positive effects on informativeness and entertainment. But perceived irritation was higher for multimedia push advertising (MMS) because of distraction and cognitive overload (Xu et al, 2009), partly contradicting the results of Cheng et al (2009), who found MMS less irritating than SMS. Integration of SMS and multimedia pull advertising as mobile websites, seems like a straight forward approach to minimize consumer irritation of mobile pull advertising while combining multimedia effects on informativeness and entertainment.…”
Section: Perceived Sacrificesmentioning
confidence: 78%
“…Comparing MMS with SMS, multimedia appeared to have positive effects on informativeness and entertainment. But perceived irritation was higher for multimedia push advertising (MMS) because of distraction and cognitive overload (Xu et al, 2009), partly contradicting the results of Cheng et al (2009), who found MMS less irritating than SMS. Integration of SMS and multimedia pull advertising as mobile websites, seems like a straight forward approach to minimize consumer irritation of mobile pull advertising while combining multimedia effects on informativeness and entertainment.…”
Section: Perceived Sacrificesmentioning
confidence: 78%
“…Features such as locationbased advertising are on the rise and advertisers have started adapting their ads to the digital users' behaviour (Xu, Oh, & Teo, 2009). Research regarding the various options for addressing users directly and via personalized approaches (Barnes & Hair, 2009) has paved the way for new advertising approaches.…”
Section: Expectations Of Advertisers' In a Digital Worldmentioning
confidence: 99%
“…Lastly, it drives offline sales to increase brand loyalty and impulse purchases. [77]. The study conducted by Chang and Theng (2013) found that potential customer attitudes towards location-based services were negatively affected by irritation, which includes inappropriate information loading and timing.…”
Section: Types Of Location-based Service Applicationsmentioning
confidence: 99%